GeospaceLAB ... - Cai, Lei (Zenodo, 2024)
A python-based library to collect, manage, and visualize geospace data (e.g. OMNI, geomagnetic indices, EISCAT, DMSP, SWARM, TEC, AMPERE, etc.). ... : If you use this software, please cite it as below. ...